2018
DOI: 10.1016/j.jacc.2018.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in SGLT1, Glucose Tolerance, and Cardiometabolic Risk

Abstract: BACKGROUND Loss-of-function mutations in the SGLT1 (sodium/glucose co-transporter-1) gene result in a rare glucose/galactose malabsorption disorder and neonatal death if untreated. In the general population, variants related to intestinal glucose absorption remain uncharacterized. OBJECTIVES The goal of this study was to identify functional SGLT1 gene variants and characterize their clinical consequences. METHODS Whole exome sequencing was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 36 publications
(43 reference statements)
4
51
1
2
Order By: Relevance
“…The role of SGLT1 at many of these sites, as well as the consequences of SGLT1 inhibition, are poorly understood. A recent study, by using a Mendelian randomization strategy, showed that SGLT1 blockade should decrease the incidence of heart failure . Regarding the role of cardiac SGLT1, several mechanisms, including but not limited to, sodium influx replenishing adenosine triphosphate (ATP) stores, glycogen accumulation, generation of reactive oxygen species and toxic accumulation of calcium have been speculated to contribute to SGLT1's role in cardiac physiology and pathophysiology.…”
Section: Sglt1 Inhibition Beyond the Kidney And Intestinementioning
confidence: 99%
“…The role of SGLT1 at many of these sites, as well as the consequences of SGLT1 inhibition, are poorly understood. A recent study, by using a Mendelian randomization strategy, showed that SGLT1 blockade should decrease the incidence of heart failure . Regarding the role of cardiac SGLT1, several mechanisms, including but not limited to, sodium influx replenishing adenosine triphosphate (ATP) stores, glycogen accumulation, generation of reactive oxygen species and toxic accumulation of calcium have been speculated to contribute to SGLT1's role in cardiac physiology and pathophysiology.…”
Section: Sglt1 Inhibition Beyond the Kidney And Intestinementioning
confidence: 99%
“…In the general population, the functional consequences of variants related to intestinal glucose absorption are uncharacterized. Seidelmann et al . therefore attempted to identify SGLT1 variants and to describe their clinical consequences.…”
Section: Carbohydratesmentioning
confidence: 99%
“…therefore attempted to identify SGLT1 variants and to describe their clinical consequences. Seidelman et al . concluded that missense variants in SGLT1 protect from diet‐induced hyperglycemia in numerous populations.…”
Section: Carbohydratesmentioning
confidence: 99%
“…The slower mean increment of BG in the administration of sodium dextrose solution can be partly explained by the fact that SGLT-1 is a rate limiting pathway for enterocyte glucose absorption. SGLT-1 uses a transmembrane sodium gradient to carry out the cellular uptake (44). Such a situation may occur slower, considering the condition of soccer players is not in the actual match condition (45), suggesting lesser sodium loss through sweat perspiration that may give a result in a weaker sodium transmembrane gradient (46) (47).…”
Section: Discussionmentioning
confidence: 99%